Pedro Nolasco Baptista: biographical data and musical activities in Pernambuco (1832-1865) (Orfeu, 2018)
The article presents the trajectory and musical activities of a musician who worked in Pernambuco between the 1830s and 1860s: Pedro Nolasco Baptista (? - 1865). A multi-talented character, Nolasco worked in the court of Rio de Janeiro and also in the province of Ceará, but it was in his hometown, Recife, that he achieved prestige and recognition, working as a performer, composer, conductor and teacher. The method consisted in the survey, cataloging and critical analysis of more than 60 unpublished sources collected in eighteenth-century Brazilian periodicals. The results indicate the significant insertion of this artist in the musical scene of his time.
Keywords: Musical sources in newspapers from Pernambuco; Pernambuco musicians of the nineteenth century; Pedro Nolasco Baptista; Oficleide in the nineteenth century